Urgensi Perlunya Pembaharuan Hukum Acara Pidana Nasional di Indonesia yang Lebih Responsif - M Zen Abdullah (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
In accordance with the background of research on  "urgency need to reform national criminal event law in Indonesia more responsive ", so it can be taken the formulation of problems that will be Diba-has, namely; Is it necessary to update the law of national criminal event in Indonesia that is more responsive in the face of the Perkem-bangan of law and globalization era at present urgency is done renewal of national criminal event law in Indonesia more responsive, Because criminal proceedings Law (KUHAP) is deemed to be inappropriate with changes in the system of governance and legal developments in the community, especially in the practice of handling criminal acts that become officers of law enforcement officials to Complete the work properly and fairly, and the second the development of the law and the change of political map coupled with economic development, transportation and technology that also affects the global meaning and existence of the substance KUHAP, So it needs to be done renewal with a more accommodating, responsive and aspirational criminal event law. In the framework of law enforcement oriented with legal and dimensional justice. The KUHAP draft must be able to provide protection and recognition to the rights of the law and restrict the actions of the legal Officer in the settlement and handling of criminal acts and may be conjoined with global demands, accordance with the conventions that have been ratified by Indonesia.